Centro- Núcleo logístico y de abasto agroindustrial Luelos (2019)
The project is taken as a basis for the analysis at the regional level of the Bogotá-Tunja corridor with respect to Sogamoso and the industrial-level corridor of the same and the other that is with respect to and reference to the project to be carried out in the south-western part of Sogamoso near the quarries and the main access roads. In relation to the development plan and the Territorial Land Use Plan (TEP) of Sogamoso, aspects such as: environmental, economic, industrial and mobility infrastructure are studied, which allow to have a productive advance in the labor sectors and facilitates the knowledge of what factors could help the development of the area taking into account the factors of contamination with respect to industries and income through agricultural products that occur between regions and municipalities as well as arriving directly at Bogotá as a means of production. A proposal was designed to improve economic and functional conditions within the agro-industrial corridor of Boyacá; proposing a master plan where the regional, municipal and local impact is determined, to promote the growth and development of the municipality of Sogamoso. From this consolidates a transformation of the current functional state and urban fabric, where a partial plan called "Eco-industrial fabric" is implemented, counting on approximately 25 hectares, in the suburban zone (south-west of the city) taking into account The expansion of type 4G roads for the main function of industrial relationship present in the region, through the implementation of functional systems to ensure the citizen a high quality of life, where the needs of growth demanded by the city are met.